Flexible working in Scottish local authority property: Moving on to the highest flexibility level - Khamkanya, Thadsin; Sloan, Brian (International Journal of Strategic Property Management, 2009)
Flexible working has emerged as a modern concept for managing office resources more effectively, efficiently, and economically. The highest level of flexible working environment, a non‐territorial working environment, can provide the best opportunity to an organization managing its office area more effectively. Moreover, staff can work in the most suitable place and time. However, in the context of public offices like Scottish Local Authorities, the most flexible working concept is not particularly welcomed at present. Cultural change, inadequate support services, including information and communication technology, working schemes, and alternative working policies are the main barriers. To overcome these barriers, the Authorities need to strategically provide adequate support to staff. Moreover, promoting a good perception towards flexible working culture at appropriate levels within an organisation could be the right strategy for preventing cultural change problems.First Publish Online: 18 Oct 2010